intercultural expressions in the yoruba native air tradition of rev. canon j. j. ransome-kuti (2020)
The evolution of indigenous Yoruba Church music can be traced to the activism of some pioneer Church men who were passionate about generating appropriate idioms and medium for musical expression. Rev. Canon Josiah Jesse Ransome-Kuti can be regarded as a progenitor of the Yoruba native air tradition in Christian liturgy. This paper employed the theory of interculturalism in identifying the elements of intercultural expressions in his musical output that formed the appendix of the Yoruba Hymn book Iwe Orin Mimo fun Ijo Enia Olorun ni ile Yoruba. His upbringing showcases simultaneous exposure to the worlds of Yoruba traditional and European Church music. Intercultural expressions identified in the song collection of Canon Kuti includes documentation, set keys, instrumentation and rhythm, harmonic progression, structural form, as well as open air music performance.